Analysis and Construction Management of Maintenance in Residential Buildings by Mobile Application - Muhammad Waheed; Mutahir Abbas (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Building problems are a regular occurrence, particularly in older residential buildings. One of the variables that contribute to a building's bad state is insufficient maintenance management. People are also responsible for the building's poor maintenance, with the authorities in charge of its conservation. The purpose of this study is to support customers and clients in their efforts to raise maintenance standards in Pakistan. This study works on the core ideas of construction management with a focus on using mobile to improve the effectiveness and standard of residential construction. The suggestions and observations included in the conclusions should be taken into account while performing such a task in action. An effective technique to do repairs and maintenance, which are constantly needed in buildings, particularly residential buildings, can be found in mobile applications. This study focuses on how mobile applications can improve work quality and reduce completion times.